Increasing Students' Speaking Ability Using OutdoorActivities At The Seventh Year Of SMP PGRI 13Gondangrejo In 2011/2012 Academic Year - AWALIATURRAHMAWATI, DEWI (2012)
The objectives of the study are as follows: 1) to clarify whether or not outdoor activities can increase the students' speaking ability, 2) to describe the implementation of outdoor activities in increasing students' speaking ability, 3) to identify the strength and weakness outdoor activity in increasing students' speaking ability for the seventh year students of SMP PGRI 13 Gondangrejo in 2011/2012. It is Classroom Action Research (CAR) conducted for the seventh year students of SMP PGRI 13 Gondangejo in 2011/2012. Consist of 31 students. The research required four procedure : planning, implementing, observing, reflecting. The data are taken from event, and document The methods of collecting data are observation, test, interview, document. In this research the writer conducts three cycles. The results of the study show that: 1) The outdoor activity understanding can increase the students' speaking ability. It is proved by the students' average score which increased after having some steps conducted by the teacher. 2) The use of outdoor activity understanding in increasing students' speaking ability is effective. The effectiveness can be proved by the increase of students' score throughout the cycle, 3) The problems occurred in the implementation of teaching speaking using outdoor activity came from both the student and the teacher. The students were having troubles because they had a lack of vocabulary, and 4) The advantages of teaching speaking using outdoor activity were that the students became easier in mastering speaking. It was due to the fact that the teachinglearning process was based on the application of speaking. The weakness of the teaching speaking using outdoor activity was time consuming since it needed more time to discuss.